Four New Iridoid Metabolites Have Been Isolated from the Stems of Neonauclea reticulata (Havil.) Merr. with Anti-Inflammatory Activities on LPS-Induced RAW264.7 Cells - Chang, Fang-Pin (Molecules, 2019)
One new iridoid, namely neonanin C (1) one monocyclic iridoid ring-opened derivative namely neonanin D (2), two new bis-iridoid derivatives namely reticunin A (3) and reticunin B (4) with sixteen known compounds (5–20) were isolated from the stems of Neonauclea reticulata (Havil.) Merr. These new structures were determined by the detailed analysis of spectroscopic data and comparison with the data of known analogues. Compounds 1–20 were evaluated for inhibition of nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages cell line. The results showed that all compounds exhibited no obvious cytotoxicity compared to the control group and five compounds including isoboonein (7), syringaresinol (10), (+)-medioresinol (12), protocatechuic acid (14) and trans-caffeic acid (15) exhibited inhibitory activities with IC(50) values at 86.27 ± 3.45; 9.18 ± 1.90; 76.18 ± 2.42; 72.91 ± 4.97 and 95.16 ± 1.20 µg/mL, respectively.